THE EFFECTIVENESS OF SCIENCE LITERACY TO IMPROVE SCIENCE ACHIEVEMENT - Avikasari Avikasari; Rukayah Rukayah; Mintasih Indriayu (Jurnal Kependidikan, 2018)
AbstractThis study was aimed at determining the effectiveness of the use of science literacy teaching materials on improving science learning achievement of fourth grade elementary school students. The method used was research and development. The quasi-experimental with simple random sampling was used to select the sampling. In the implementation of the test, two sample groups were used, namely the experimental group and the control group. The testing phase of this product was carried out in two elementary schools in Gunungpati sub-district with a sample of 56 students of grade IV elementary school in the 2017/2018 school year. They consisted of 30 students of elementary school A and 26 students of elementary school B. The data were collected using tests. The results show that science-based science literacy teaching materials were effective in improving student learning achievement with the t-test calculation of 0.031. The results of the t test prove the difference between pretest and posttest values in the control and experimental groups. It can be concluded that the use of science teaching materials based on science literacy is effective to improve science learning achievement of fourth grade elementary school students.KEEFEKTIFAN PENGGUNAAN BAHAN AJAR SCIENCE LITERACY TERHADAP PENINGKATAN PRESTASI BELAJARAbstrakPenelitian ini bertujuan untuk mengetahui keefektifan penggunaan bahan ajar science literacy terhadap peningkatan prestasi belajar IPA siswa kelas IV sekolah dasar. Penelitian ini adalah penelitian dan pengembangan. Penelitian menggunakan metode eksperimen semu (Quasi-eksperimental) dengan simple random sampling. Dalam pelaksanaan pengujian digunakan dua kelompok sampel, yaitu kelompok eksperimen dan kelompok kontrol. Tahap pengujian produk ini laksanakan pada dua sekolah dasar di kecamatan gunungpati dengan sampel adalah 56 siswa kelas IV sekolah dasar pada Tahun Ajaran 2017/2018 yang terdiri atas 30 siswa SD A dan 26 siswa SD B. Data dikumpulkan menggunakan tes. Hasil penelitian menunjukkan bahwa bahan ajar IPA berbasis science literacy efektif meningkatkan prestasi belajar siswa dengan hasil perhitungan uji-t sebesar 0,031. Hasil uji-t tersebut membuktikan adanya perbedaan nilai pretest dan posttest pada kelompok kontrol dan eksperimen. Jadi dapat disimpulkan bahwa penggunaan bahan ajar IPA berbasis science literacy efektif untuk meningkatkan prestasi belajar IPA siswa kelas IV sekolah dasar.